3D Woven Textile Structural Polymer Composites: Effect of Resin Processing Parameters on Mechanical Performance - Mishra, Rajesh Kumar; Petru, Michal; Behera, Bijoya Kumar; Behera, Promoda Kumar (Polymers, 2022)
This work presents the manufacture of polymer composites using 3D woven structures (orthogonal, angle interlock and warp interlock) with glass multifilament tows and epoxy as the resin. The mechanical properties were analyzed by varying the processing parameters, namely, add-on percentage, amount of hardener, curing time, curing temperature and molding pressure, at four different levels during the composite fabrication for three different 3D woven structures. The mechanical properties of composites are affected by resin infusion or resin impregnation. Resin infusion depends on many processing conditions (temperature, pressure, viscosity and molding time), the structure of the reinforcement and the compatibility of the resin with the reinforcement. The samples were tested for tensile strength, tensile modulus, impact resistance and flexural strength. Optimal process parameters were identified for different 3D-woven-structure-based composites for obtaining optimal results for tensile strength, tensile modulus, impact resistance and flexural strength. The tensile strength, elongation at break and tensile modulus were found to be at a maximum for the angle interlock structure among the various 3D woven composites. A composition of 55% matrix (including 12% of hardener added) and 45% fiber were found to be optimal for the tensile and impact performance of 3D woven glass-epoxy composites. A curing temperature of about 140 °C seemed to be optimal for glass-epoxy composites. Increasing the molding pressure up to 12 bar helped with better penetration of the resin, resulting in higher tensile strength, modulus and impact performance. The optimal conditions for the best flexural performance in 3D woven glass-epoxy composites were 12% hardener, 140 °C curing temperature, 900 s curing time and 12 bar molding pressure.
Keywords: textile structural composite; curing temperature; curing time; amount of hardener (%); molding pressure; add-on (%); mechanical properties; epoxy resin